Energy Storage Materials Using Metal Boranes as Solid-State Electrolytes - Hales, Thomas Adam (Curtin University, 2024)
The need for improved battery technologies is increasing worldwide. This project focuses on the synthesis of alkali metal substituted cluster borohydride salts and their possible usage in solid-state battery technologies. A library of dodecaborate salts with heavy metal substitutions were successfully synthesised and characterised with many of these compounds found to have promising superionic conductivities and comparable stabilities at elevated temperatures.